Rethinking Service Systems and Public Policy: A Transformative Refugee Service Experience Framework. Issue 2 (April 2021) - Boenigk, Silke; Fisk, Raymond; Kabadayi, Sertan; Alkire, Linda; Cheung, Lilliemay; Corus, Canan; Finsterwalder, Jörg; Kreimer, Aaron A.; Luca, Nadina; Omeira, Mansour; Paul, Pallab; Santos, Marcos F.; et al.
The global refugee crisis is a complex humanitarian problem. Service researchers can assist in solving this crisis because refugees are immersed in complex human service systems. Drawing on marketing, sociology, transformative service, and consumer research literature, this study develops a Transformative Refugee Service Experience Framework to enable researchers, service actors, and public policy makers to navigate the challenges faced throughout a refugee's service journey. The primary dimensions of this framework encompass the spectrum from hostile to hospitable refugee service systems and the resulting suffering or well-being in refugees' experiences. The authors conceptualize this at three refugee service journey phases (entry, transition, and exit) and at three refugee service system levels (macro, meso, and micro) of analysis. The framework is supported by brief examples from a range of service-related refugee contexts as well as a Web Appendix with additional cases. Moreover, the authors derive a comprehensive research agenda from the framework, with detailed research questions for public policy and (service) marketing researchers. Managerial directions are provided to increase awareness of refugee service problems; stimulate productive interactions; and improve collaboration among public and nonprofit organizations, private service providers, and refugees. Finally, this work provides a vision for creating hospitable refugee service systems.